The Macleaya cordata Symbiont: Revealing the Effects of Plant Niches and Alkaloids on the Bacterial Community - Lei, Fangying; Liu, Xueduan; Huang, Haonan; Fu, Shaodong; Zou, Kai; Zhang, Shuangfei; Zhou, Li; Zeng, Jianguo; Liu, Hongwei; Jiang, Luhua; Miao, Bo; Liang, Yili (Frontiers in Microbiology, 2021)
Endophytes play an important role in plant growth and health. Therefore, exploring the bacterial community variation at the plant niche-level is essential to understand the microbe-plant interactions. This study used 16S rRNA gene analysis to investigate the microbial structure and composition of rhizosphere soil and different organs of the Macleaya cordata. The results indicated that bacteria community structure varied widely among compartments. Bacterial diversity and richness in the rhizosphere soil were significantly higher than in plant parts. Some bacteria with high abundance in rhizosphere soil, such as Acidobacteria, Bacteroidetes, and Gemmatimonadetes, gradually decreased from roots to fruit. We also measured the alkaloid content in plant tissues. Correlation tests showed that alkaloids affected the microorganisms in different niches, with Sphingomonas showing a significant positive correlation with sanguinarine and chelerythrine. In addition, the low alkaloid content in stems may explain their higher bacterial diversity. The analysis of Picrust2 indicates that the synthesis of plant alkaloids might lead to a higher abundance of genes related to alkaloid metabolism in endophytic microorganisms.